2009
DOI: 10.1007/s12640-009-9020-6
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Nucleotide Receptor is Coupled to GSK-3 Inhibition and Neuroprotection in Cerebellar Granule Neurons

Abstract: In this study we report the coupling of nucleotide receptors to GSK-3 signalling, a relevant survival pathway in cerebellar granule neurons. P2X 7 agonist BzATP induced a 3-4-fold increase in GSK-3 phosphorylation, which is reported to be associated with the catalytic activity inhibition. This effect was dependent on extracellular calcium and PKC, and independent of PI3-K (phosphatidyl-inositol-3-kinase)/Akt, the main survival route of neurotrophins. BzATP also prevented the apoptosis of granule neurons induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 66 publications
8
35
0
Order By: Relevance
“…The speed with which β-catenin is activated suggests that P2X7 regulates the stability of β-catenin as opposed to its gene expression at early time points. In this regard, we showed that P2X7 activation in osteoblast-like cells rapidly inhibits GSK3β in a PKCdependent manner in agreement with previous findings in cerebellar granule neurons [13,22]. Interestingly, the PTH-PTH 1 receptor complex has also been shown to facilitate canonical Wnt signaling through inhibition of GSK3β in osteoblast-like SaOS-2 cells [28].…”
Section: P2x7 Potentiates the Wnt/β-catenin Pathwaysupporting
confidence: 92%
See 4 more Smart Citations
“…The speed with which β-catenin is activated suggests that P2X7 regulates the stability of β-catenin as opposed to its gene expression at early time points. In this regard, we showed that P2X7 activation in osteoblast-like cells rapidly inhibits GSK3β in a PKCdependent manner in agreement with previous findings in cerebellar granule neurons [13,22]. Interestingly, the PTH-PTH 1 receptor complex has also been shown to facilitate canonical Wnt signaling through inhibition of GSK3β in osteoblast-like SaOS-2 cells [28].…”
Section: P2x7 Potentiates the Wnt/β-catenin Pathwaysupporting
confidence: 92%
“…In the present study, we provide the first evidence that activation of P2X7 potentiates Wnt/β-catenin signaling. Stimulation of the ADP-sensitive P2Y 13 receptor has also been shown by others to promote β-catenin nuclear localization in cerebellar granule neurons [26]. Given that transcripts for P2Y 13 are present in MC3T3-E1 cells and rodent calvarial osteoblasts [27], it is possible that P2Y 13 may also modulate canonical Wnt signaling in our system.…”
Section: P2x7 Potentiates the Wnt/β-catenin Pathwaysupporting
confidence: 61%
See 3 more Smart Citations